FRET Enabled Light Harvesting within Quantum Dot Loaded Nanofibers - Altintas, Yemliha; Kiremitler, Nuri Burak; Genc, Sinan; Onses, M. Serdar; Mutlugun, Evren (IOP Publishing Ltd, 2018)
The spatial control of the nano-emitters in novel light harvesting platforms offers great potential for the manipulation of the excitonic interaction amongst the donor-acceptor pairs of energy transferring agents. In this work, we report colloidal quantum dot loaded electrospun nanofibers as a light harvesting platform to study the excitonic interaction among them. The donor emission lifetime modified from 12.46 ns to 7.45 ns with the change in the ratio of green and red quantum dots in the nanofiber, as a result of confining acceptor quantum dots in close proximity. The spectrally narrow emitter luminescent nanofiber platforms have further been investigated for their potential of white light generation. The hybrid platform of blue LED integrated electrospun nanofibers has been shown to demonstrate a correlated color temperature of 3632.5 K, luminous efficacy of optical radiation value of 307.7 lm/W-opt along with color rendering index value of 60.
Mutlugun, Evren/0000-0003-3715-5594; Onses, Mustafa Serdar/0000-0001-6898-7700; Kiremitler, N. Burak/0000-0001-6065-4899; Genc, Sinan/0000-0002-6909-723X;
Keywords: Colloidal Quantum Dots; Photoluminescence; Nanofiber; White Light